The acts of the M23 committed on Congolese territory as the constitutive foundations of the international criminal responsibility of Paul KAGAME as a military superior - MALANGU MPOSHY KASAMBULE, Daddy (Revue Internationale du Chercheur, 2025)
Abstract The Rome Statutes are very demanding regarding the criminal responsibility of military superiors; the conditions are clear. Applying them to the case unfolding in the Democratic Republic of Congo, the problem is obvious given that the Rwandan army provides the M23 with weapons, personnel, and strategy, and is thus given the designation of auxiliary force. It turns out that this would logically lead to Mr. Paul Kagame being held responsible, as the military superior, for the acts of genocide perpetrated in the DRC, given his status within the Rwandan Republic and the state resources at his disposal.